Interprofessional learning, impression management, and spontaneity in the acute healthcare setting. Issue 5 (2nd September 2016) - Bell, Elaine; McAllister, Sue; Ward, Paul R.; Russell, Alison
ABSTRACT: Spontaneous learning is integral to definitions of interprofessional learning (IPL) because it has been suggested that spontaneous learning can be deeply connected with the work that people do in collaboration with colleagues via their professional networks. However, its nature and the processes involved are not well understood. Goffman's theory of impression management offers a useful theoretical framework to consider the way in which interaction in the workplace connects to spontaneous learning. This article explores the current literature to investigate the usefulness of this framework to better understand and identify spontaneous learning in the workplace. Aspects such as the connections between spontaneous learning occurring in formal and informal work activities, the spaces in which it occurs, and the influence of professional networking are considered. It is proposed that research directed to developing a better understanding of the nature of spontaneous learning in IPL will assist in connecting this learning to formal IPL curricula, enhancing IPL and patient outcomes